Dipole control of Rashba spin splitting in a type-II Sb/InSe van der Waals heterostructure. (28th October 2020) - Wang, Donghui; Ju, Weiwei; Li, Tongwei; Zhou, Qingxiao; Zhang, Yi; Gao, Zijian; Kang, Dawei; Li, Haisheng; Gong, Shijing
Abstract: InSe monolayer, belonging to group III–VI chalcogenide family, has shown promising performance in the realm of spintronic. Nevertheless, the out-of-plane mirror symmetry in InSe monolayer constrains the electrons' degrees of freedom, and this will confine its spin-related applications. Herein, we construct Sb/InSe van der Waals heterostructure to extend the electronic and spintronic properties of InSe. The density functional theory is utilized to verify the tunable electronic properties and Rashba spin splitting (RSS) of Sb/InSe heterostructure. According to the obtained results, the Sb/InSe heterostructure can be considered as a direct band gap semiconductor with typical type-II band alignment, where the electrons and holes are localized in the InSe and Sb layers, respectively. The RSS is recognized at conduction band minimum around Γ point in Sb/InSe, which is induced by the spontaneous internal electric field with electric dipole moment of 0.016 e Å from Sb to InSe. The vertical strain, in-plane strain, and external electric field are employed to modulate the strength of RSS. The Rashba coefficient and dipole moment exhibit the similar variation tendency, suggesting the strength of RSS depends on the magnitude of dipole moment. The controllable RSS makes Sb/InSe heterostructure become an appropriate candidate material for spintronic devices.